المناخ الأسري لدى طلبة جامعة غرداية (El-Wahat Journal for Research and Studies, 2025)
Our study aimed to know the level of family climate among university students, and to know the differences between the sexes in the family climate ,the study consisted of (120) male and female students,(67) males and (53) females, to collect information, then rely on the family climate scale by Muhammad bayoumi  khalil ,the study reached the following results :• Ghardaia university students enjoy a good family climate.• There are statistically significant differences in family climate between males and females.Key words:  family climate, university students.